2023
DOI: 10.1039/d3fo01016c
|View full text |Cite
|
Sign up to set email alerts
|

Phenolamide extract of apricot bee pollen alleviates glucolipid metabolic disorders and modulates the gut microbiota and metabolites in high-fat diet-induced obese mice

Abstract: Phenolamide alleviates glucolipid metabolic disorders and modulates gut microbiota and metabolites in high-fat diet-induced obese mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Hydroxycinnamic acids usually present cis–trans isomers, thus resulting in multiple isomers of CPAs, such as tri- p -coumaroyl spermidine isomers in Lycium berry and bee pollen. , Generally, HRMS is unable to differentiate between cis and trans isomers. In recent years, Seon Beom Kim and his colleagues have identified some cis–trans isomers of CPAs through nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Identification Sources and Quantities Of Cpasmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydroxycinnamic acids usually present cis–trans isomers, thus resulting in multiple isomers of CPAs, such as tri- p -coumaroyl spermidine isomers in Lycium berry and bee pollen. , Generally, HRMS is unable to differentiate between cis and trans isomers. In recent years, Seon Beom Kim and his colleagues have identified some cis–trans isomers of CPAs through nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Identification Sources and Quantities Of Cpasmentioning
confidence: 99%
“…There is relatively limited research concerning the modulation of gut microbiota by CPAs. Recently, research indicated that CPAs (especially tri- p -coumaroyl spermidine) from apricot bee pollen can counteract the elevation in the Firmicutes/Bacteroidetes ratio observed in mice fed an HFD . Furthermore, CPAs promoted the proliferation of beneficial bacteria like Muribaculaceae and Parabacteroides while concurrently diminishing the presence of detrimental bacteria such as Peptostreptococcaceae and Romboutsia .…”
Section: Functional Properties Of Polyaminesmentioning
confidence: 99%
See 3 more Smart Citations